ESSENCE OF NATIONAL EDUCATION - Mamarajabova Yulduz Chorshanbi qizi; Bobomurodov Sirojiddin (Journals Park Publishing, 2023)
In this article, the content and essence of national education, National consciousness, ideology. The harmony of humanitarian education in national education is given.
Keywords: Educational work, conceptual, independence is the basis of spirituality, pride, respect for national values, freedom and liberty, humanitarianism, brotherhood and cooperation, love for science, faith and belief.